Impact of instrumental ties, tacit knowledge sharing and affective commitment on absorptive capacity – an empirical study of pharmaceutical companies. Issue 2 (1st February 2019) - Rafique, Muhammad; Hameed, Shafqat; Agha, Mujtaba Hassan
ABSTRACT: Absorptive capacity construct has gained importance since last two decades especially in knowledge intensive environment. The companies invest their time and resources to achieve strategic goals and thus enhance their absorptive capacity in order to deal with new knowledge requirements. Companies largely focus on the macro level processes and mechanisms which are external to their boundaries and ignore the intra company factors critical to absorptive capacity. This study explores the impact of human behaviours related to instrumental ties (INST), affective commitment (AFC) and tacit knowledge sharing (TKS) on absorptive capacity (ACAP). Results of this study based on sample from pharmaceutical companies of Pakistan show significant contribution of human behaviour in development of absorptive capacity. The employees' behaviours may not be ignored by decision makers in pharmaceutical companies while formulating knowledge strategies.